Urban Renewal in Istanbul: Reconfigured Spaces, Robotic Lives. (30th July 2012) - Karaman, Ozan
Abstract The article discusses Turkey's property‐led residential redevelopment model. This entails the demolition of an existing settlement, replacing it with blocks of apartments (usually constructed on the exact same site and at a higher density), some of which are then made available to displaced residents for purchase via mortgage loans with long maturities. While the authorities promote this model of urban renewal as an innovative public housing policy, I argue that, far from being an exception to market‐rate housing, the model is in fact a market‐disciplinary tool. It seeks to incorporate into the formal market not just spontaneously developed and only partially regulated spaces, but also the conduct of residents living in these informal neighborhoods. The article contributes to the immense literature on urban renewal and organized struggles around the right to housing by showing that urban renewal is not simply about dispossession and displacement. In the Turkish case, urban renewal does not necessarily seek to displace poor residents (even though it often ends up doing so), rather to incorporate them into a nascent mortgage origination market. The second half of the article introduces and elaborates on a case study in Istanbul.